The places of the different in contemporary work: work trajectories of LGBT people (Cadernos de Psicologia Social do Trabalho, 2020)
This paper analyzes the experiences of a group of LGBT workers who visibly do not comply with heteronormative standards, in order to understand their perceptions about the labor market, the ways they use to deal with adversities and the meanings they attribute to work. In contemporary society, which is hegemonically heteronormative, conservative and neoliberal, LGBT people are marginalized in different areas of social life, especially at work. Sexual and gender identities are understood as historical, cultural and performance constructs that political and economic transformations have tried to deny by reaffirming the existence of a heterosexual matrix that regulates sexualities and the constitution of subjects considered apt for the job. However, for the interviewed group, working, in addition to guaranteeing social reproduction, means both experiencing constraints, suffering and prejudices and, through daily struggle, learning to overcome barriers, self-affirming identities and expressions of gender, experiencing the recognition and the exercise of citizenship, which translates to an additional effort for survival.